Pengaruh Karakteristik Individu Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT.Cahaya Aspal Buton (CAB) - Nuriati, Nuriati; Hajar, Ibnu; Amin, Moh. (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
This study aims to (1) determine the effect of individual characteristics and work environment on employees' performance at PT. Light Asphalt Buton (CAB); (2) to determine the effect of individual characteristics on the performance of employees at PT. Light Asphalt Buton (CAB); (3) to determine the effect of the working environment on employees' performance at PT. Light Asphalt Buton (CAB). The population in this study were all employees at PT. Buton Asphalt light, which amounted to 32 people and all the population as respondents or census method that investigators can reach. The data collection method in this study are a questionnaire, and the raw data collected was analyzed with multiple linear regression using IBM SPSS Statistics 20. The results showed that (1) The individual characteristics and work environment significantly affect the performance of employees at PT. Light Asphalt Buton (CAB); (2) The individual characteristics of positive and significant effects on the performance of employees at PT. Light Asphalt Buton (CAB); (3) The working environment has a positive and significant effect on the performance of employees at PT. Light Asphalt Buton (CAB.